Chlamydophila psittaci infections in hyacinth macaws (anodorhynchus hyacinthinus) confiscated in Brazil - Raso, Tânia Freitas; Teixeira, Rodrigo Hidalgo Friciello; Carrasco, Adriano Oliveira Torres; Júnior, João Pessoa Araújo [UNESP]; Pinto, Aramis Augusto [UNESP] (American Association of Zoo Veterinarians, 2013)
The hyacinth macaw (Anodorhynchus hyacinthinus) is the largest species of psittacine birds. It is considered endangered and illegal trade is one of the main factors involved in its decline. In this study, 26 hyacinth macaws maintained under poor husbandry conditions and destined for the illegal trade were confiscated in São Paulo State, Brazil. These birds were evaluated for the presence of antibodies against Chlamydophila psittaci by complement fixation test and C. psittaci DNA by seminested polymerase chain reaction. Results showed that 65.4% of the macaws were positive for at least one test. Birds with subclinical infections can shed chlamydiae intermittently over long periods, contributing to the dissemination of the agent. Global trade is one of the most important drivers of disease emergence. The high percentage of positive samples in this study emphasizes the potential risk that the illegal trade of wild birds represents for both human and animal health. Copyright 2013 by American Association of Zoo Veterinarians.
Keywords: Anodorhynchus hyacinthinus; chlamydiosis; Chlamydophila psittaci; hyacinth macaw; illegal trade; bacterium antibody; animal; animal disease; bird disease; blood; Brazil; commercial phenomena; crime; environmental protection; isolation and purification; methodology; microbiology; ornithosis; polymerase chain reaction; psittacine; Animals; Antibodies, Bacterial; Bird Diseases; Commerce; Conservation of Natural Resources; Crime; Polymerase Chain Reaction; Psittaciformes; Psittacosis